Analisis Yuridis Tingginya Cerai Gugat Istri terhadap Suami pada Masa Pandemi Covid-19 (Studi Penelitian di Mahkamah Syarâ€™iyah Lhoksukon) - Eko Gani PG; Eka Chyntia (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
The number of divorce cases that occurred during the Covid-19 pandemic is a concern. Divorce applications at the Lhoksukon Sharia Court are mostly from ordinary or middle class people who apply for divorce for various reasons. Article 38 Law no. 1 of 1974 regarding "marriage can be broken due to death, divorce and on a court decision. Dissolution of a marriage caused by death does not require special discussion because neither party is aggrieved either recognizing their responsibilities or rights. This study aims to find out and analyze the legal arrangements for divorce between a wife and her husband during the Covid-19 pandemic from the aspects of Civil Law, the Civil Code and to find out the purpose of a wife's divorce from her husband according to the Criminal Code. In this study, the researcher wanted to see what factors influenced the parties filing for divorce that occurred during the Covid-19 period at the Lhokseumawe Syar'iyah Court, how were the efforts made by judges to reduce divorce during the Covid-19 period at the Lhokseumawe Syar'iyah Court and the obstacles what is faced in solving the problem of divorce which has increased during the covid-19 pandemic.The type of research used to answer these problems is juridicalempirical legal research using an empirical approach. Data collection was carried out through interview studies and field research. Data analysis used is qualitative analysis. The results show that Divorce is increasing due to economic problems, infidelity and domestic violence, and families are facing problems leading to lawsuits for divorce. The high number of divorces during the Covid-19 pandemic can be overcome through preventive efforts, namely preventing unwanted things such as divorce from happening in the future. HinderingÂ the resolution of high divorce cases is the strong desire of the parties to maintain the divorce and third party intervention to help couples feel more confident about their divorce.